2001
DOI: 10.1097/00005768-200102000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Muscle function in 164 men and women aged 20???84 yr

Abstract: These results thus suggest that muscle strength losses would be mainly due to a decline in muscle mass in both genders, whereas age-related decline in muscle function in men may also be the result of neural factors, such as muscle recruitment and/or specific tension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
139
1
8

Year Published

2002
2002
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 214 publications
(160 citation statements)
references
References 16 publications
9
139
1
8
Order By: Relevance
“…These results suggest that the effects of aging on muscle shortening velocity might become apparent after 50 years of age. Using male and female subjects ranging in age from 20 to 84 years old, Akima et al (2001) measured velocity values at 0, 60, 180 and 300 degrees per second by the leg extensor and flexor muscles using an isokinetic machine, and they reported that all velocity values decreased with aging. Similar results were also reported by Frontera et al (1991) with male and female subjects aged 45-78 years old.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that the effects of aging on muscle shortening velocity might become apparent after 50 years of age. Using male and female subjects ranging in age from 20 to 84 years old, Akima et al (2001) measured velocity values at 0, 60, 180 and 300 degrees per second by the leg extensor and flexor muscles using an isokinetic machine, and they reported that all velocity values decreased with aging. Similar results were also reported by Frontera et al (1991) with male and female subjects aged 45-78 years old.…”
Section: Discussionmentioning
confidence: 99%
“…For this context, many proofs have been shown by dealing with the isometric strength of various muscle groups: grip strength (Izquierdo et al (1999b), elbow flexor strength (Viitasalo et al, 1985;Doherty et al, 1993), ankle plantar strength (Vandervoort and McComas, 1986), and knee extensor strength (Larsson et al, 1979;Häkkinen and Häkkinen, 1991;Häkkinen et al, 1995;Akima et al, 2001). According to Klitgaard et al (1990), reduction due to aging in isometric strength was greater in the lower limb muscles than those in the upper limbs.…”
Section: Introductionmentioning
confidence: 99%
“…No entanto, esses estudos foram desenvolvidos com adultos jovens. Não se sabe até que ponto seus resultados poderiam ser transferidos para indivíduos idosos, uma vez que a idade se associa a um declínio gradativo das capacidades motoras, em especial da força muscular (14,15) . As respostas de fadiga observadas em pessoas idosas, portanto, não necessariamente serão similares àquelas exibidas por indivíduos jovens.…”
Section: Introductionunclassified
“…The maximum force production is strongly related to muscle mass or cross sectional area of muscle, so that the decline in maximum force production with aging can be caused by a decrease in muscle mass (Akima et al 2001). It has been reported that a 31% decrease in the volume of quadriceps femoris is seen in elderly as compared with young individuals (Trappe et al 2001).…”
Section: Aging Related Muscle Atrophy and Changes In Contractile Propmentioning
confidence: 99%